INFLUENCE OF INTERNAL CONTROLS ON FINANCIAL PERFROMANCE OF DAIRY COOPERATIVE SOCIETIES IN MERU COUNTY, KENYA - Nyaga, Emmanuel; Kiganane, Lucy; Gweyi, Moses (Advances in Social Sciences Research Journal, 2021)
Internal control systems have been a challenge to the performance of Dairy Cooperative Societies in Kenya. Incidences of total disregard to rules and procedures, adherence to cooperative management regulations have been on the rise. The ability of the management to adhere to the internal controls systems is of importance and it’s bound to affect the financial performance of the societies. The purpose of this study was to determine influence of internal control on financial performance of Dairy Cooperative Societies. The study was restricted to Dairy Cooperative Societies licensed to operate in Meru County. . The study adopted a descriptive research design and made use of purposive sampling to generate a sample of 72 respondents. A questionnaire was utilized to collect data from the respondents. Data was analyzed and evaluated through the use of descriptive statistics; standard deviation, mean and percentages, and made use of ordinary linear regression models to generate the size of effects of independent variables on the dependent variable. Analyzed data was presented in tables and pie charts. The response rate of the administered questionnaires stood at 88.88%. This response rate was found to be sufficient for inferential statistical analysis. The coefficient of determination indicated that internal control contributed 65.7% of the variation in financial performance as explained by coefficient of determination which stood at 0.657. The p-value and regression coefficient internal control generated after running the regression model was (β= 0.232, p = 0.026). These results indicate that internal controls positively and significantly influenced the financial performance of Dairy Cooperative Societies in Meru County. This study therefore, recommends the implementation of internal control mechanisms in all Dairy Cooperative Societies in Meru County.